Metformin accumulation: Lactic acidosis and high plasmatic metformin levels in a retrospective case series of 66 patients on chronic therapy*. (February 2014) - Vecchio, S.; Giampreti, A.; Petrolini, V. M.; Lonati, D.; Protti, A.; Papa, P.; Rognoni, C.; Valli, A.; Rocchi, L.; Rolandi, L.; Manzo, L.; Locatelli, C. A.
Abstract: Objective. The relationship between metformin accumulation and lactate increase is still debated. This observational case series aims to evaluate the correlation of metformin plasma levels with the pH, lactate and creatinine levels, and with the mortality rate in selected patients with metformin accumulation confirmed through metformin plasma concentration detection at hospital admission. Material and methods . All cases of lactic acidosis (pH, ≤ 7.35; arterial lactate, ≥ 5 mmol/L) related to metformin accumulation (plasma level ≥ 4 mcg/mL) from 2007 to 2011 were retrospectively reviewed. Erroneous ingestion and voluntary overdoses were excluded. Epidemiological, medical history, clinical and laboratory data were evaluated in all cases. Results . Sixty-six patients were included. Thirty-one patients (47%) had contraindication to therapy with metformin. All patients showed severe lactic acidosis (pH, 6.91 ± 0.18; lactate, 14.36 ± 4.90 mmol/L) and acute renal failure (creatinine, 7.24 ± 3.29 mg/dL). The mean metformin plasma concentration was 40.68 ± 27.70 mcg/mL. Metformin plasma concentrations showed a correlation, statistically significant even if not strong, with creatinine ( p = 0.002, R = 0.37), pH ( p < 0.0001, R = − 0.43) and plasma lactate levels ( p = 0.001, R = 0.41). Sixty-two (94%) underwent dialysis. Early mortality (before discharge from ICU) was 26% (17 cases). Lactate and metformin concentrations had mean levels not statistically different in surviving and deceased patients. Conclusions . Patients on chronic therapy with metformin may develop a mitochondrial-related toxicity that should be considered when patients present with lactic acidosis, renal failure, and frequently, a medical history of gastrointestinal manifestations during the days preceding the hospital admission. The correlation between metformin plasma concentrations and creatinine, pH, and lactate levels seems to be related to the mechanism of action (inhibition of complex I of the mitochondrial respiratory chain) and to the kinetic properties (high distribution volume and low protein binding) of the drug. The relevant early mortality seems not correlated with the levels of metformin or lactates: this could be due to the possible role of concurrent illness even if, such as for the relationships with lactate and creatinine, a more proper toxicological evaluation could be obtained by assessing metformin erythrocyte concentrations instead of the plasmatic ones.